Effet du port de semelles orthopédiques pendant la course à pied sur la posture et sur l`architecture podale - Vermand, S.; Duc, S.; Samper, J.-M.; Ferrari, F.-J.; Gaillet, J.-C.; Bertucci, W.; Polidori, G. (Movement & Sport Sciences - Science & Motricité, 2017)
Objectives: To study the effect of foot orthoses on postural control and foot measures after running. Material and methods: Twenty sportsmen (10 men and 10 women) run 30 minutes in the field at 10 km/h with using running soles or orthopaedic soles. The morphological data (navicular drop, length of foot, width forefoot), posturographic data (plantar area) and stabilometric data (Xmean, Ymean, and length of the trace, confidence ellipse area and speed of movement of center of pressure) were measured 5 minutes before and after the running exercise. Results: Foot orthoses decreased significantly navicular drop left foot (p < 0.05), increased the length of 2 feet (p < 0.05), decreased plantar area of 2 feet (p < 0.01). The pair of insoles causes a significant offset of the center of pressure to the right in the frontal plane (p < 0.01) but did not affect other postural factors. This results shows that wearing orthopaedic soles causes the hang of foot arch since the foot tends to elongate while the surface decreases. However, the asymmetrical responses observed between the two foots leads us that most orthopaedic treatment performing symmetrically can disturb the body balance and change the foot architecture.